Rhinoceros Giants : The Paleobiology of Indricotheres - Prothero, Donald R. (Book collections on Project MUSE., 2013)
Written for readers who are fascinated by the huge beasts that once roamed the earth, this book introduces the giant hornless rhinoceros, Indricotherium. These massive animals inhabited Asia and Eurasia for more than 14 million years, about 37 to 23 million years ago. They had skulls 6 feet long, stood 22 feet high at the shoulder, and were twice as heavy as the largest elephant ever recorded, tipping the scales at 44,100 pounds. Fortunately, the big brutes were vegetarians. Here, the author tells their story, from their discovery just a century ago to contemporary research on how they lived and died.